Grid frequency regulation through virtual power plant of integrated energy systems with energy storage - Tao Xu; Rujing Wang; He Meng; Mengchao Li; Yu Ji; Ying Zhang; Jianli Zhao; Jiani Xiang (IET Renewable Power Generation)
Abstract Owing to the widespread integration of renewable distributed energy resources (DERs), the system frequency stability has been jeopardized by the non‐inertial and stochastic units caused by power electronic devices. The integrated energy system (IES) that combines multi‐vector energy resources can provide energy compensation among sub‐systems in a coordinated fashion to further alleviate the volatility on the electric grid. Under the framework of IES, a virtual power plant (VPP) can aggregate multi‐entities and multi‐vector energy resources to participate in the frequency regulation service while pursuing profit maximization. A three‐stage optimal scheduling model of IES‐VPP that fully considers the cycle life of energy storage systems (ESSs), bidding strategies and revenue settlement has been proposed in this paper under the modified PJM frequency regulation market framework to motivate the aggregated resources to respond to the frequency regulation market actively. The simulation results under various scenarios have verified the feasibility and effectiveness of the proposed model through techno‐economic analysis, the advantages of IES‐VPP have been demonstrated compared with a single vector energy system.